Increasing Food Production with Aquaponic Cultivation System to Support Sustainable Economic Independence During the Covid-19 Pandemic Period, Gunungpati District, Semarang (Indonesian Journal of Devotion and Empowerment, 2022)
The COVID-19 pandemic occurred when the SARS-CoV2 virus spread throughout the world. It creates a widespread global shock that creates a severe economic slowdown. There has been a slowdown in all sectors of the economy worldwide, and more than a third of the global population has been isolated. It can harm the community and the surrounding environment, especially related to the irregular income many people receive in the village. In overcoming the economic downturn in the community, the service team provided several solutions to help reduce these problems. The solution offered by the service team is Increasing Food Production with Aquaponic Cultivation Systems. The aquaponics cultivation system is easy for rural communities to increase community income and provide benefits to individuals and the surrounding environment. The team chose one village as the place to implement the solution, namely Kalisegoro village. The method used is the active approach, namely the provision of aquaponic cultivation training. The training was carried out using used plastic bottles, tarpaulins, wood, paralon, seeds, water hoses, and planting media. Pandemi COVID-19 terjadi ketika virus SARS-CoV2 menyebar ke seluruh dunia. Ini menciptakan guncangan global yang meluas yang menciptakan perlambatan ekonomi yang parah. Telah terjadi perlambatan di semua sektor ekonomi di seluruh dunia dan lebih dari sepertiga populasi global telah diisolasi. Hal tersebut dapat memberikan dampak negatif bagi masyarakat dan lingkungan sekitar terutama terkait pendapatan tidak tetap yang diterima oleh banyak masyarakat di desa. Dalam mengatasi penurunan ekonomi masyarakat yang terjadi, tim pengabdian memberikan beberapa solusi untuk membantu mengurangi permasalahan tersebut. Solusi yang ditawarkan tim pengabdian yaitu Peningkatan Produksi Pangan Dengan Sistem Budidaya Aquaponik. Sistem budidaya aquoponik merupakan hal yang mudah bagi masyarakat desa untuk meningkatkan pendapatan masyarakat serta memberikan manfaat bagi individu maupun lingkungan sekitar. Tim memilih satu desa sebagai tempat untuk mengimplementasikan solusi tersebut yaitu desa Kalisegoro. Metode yang digunakan pendekatan aksi yaitu pemberian pelatihan budidaya aquoponik. Pelatihan dilakukan dengan memanfaatkan botol plastik bekas, terpal, kayu, paralon, bibit, selang air dan media tanam.